Well-Being, More Than a Dream: Women Constructing Metaphors of Strength - Barnard, Antoni (Frontiers in Psychology, 2018)
Research on gender inequalities in well-being, attribute lower levels of wellness in women to the burden of multiple role demands, particularly during midlife. Using quantitative measures of subjective well-being, such studies tend to narrow the concept of well-being and overlook the value of in-depth context-specific inquiry. Work-life balance is also a consistent causative narrative in studies on women’s well-being. Yet, such a narrative frequently emphasises individual agency in a seemingly unattainable quest, implying an anomaly on how women then actually manage to sustain their well-being. The present study therefore explored the work-life experiences of women in their midlife. The aim was to reach a deeper understanding of the psycho-social dynamics at play in sustaining a psychologically-well self. Meta-theoretically the study built on non-traditional and gendered career models that augment female employees’ unique career needs. From a socioanalytic stance, this study investigated secondary data gathered from focus groups, which were based on the socioanalytic method of social dream drawing. The data originated from four sessions of social dream drawings, in which the researcher as participant-observer, investigated work-life experiences of seven women. The gathered information was managed through Atlas.ti and processed through phenomenological hermeneutic analysis. The findings contribute to the discourse on women and well-being and give insight into the application of a unique socioanalytic methodology to research in this field from a gendered perspective. Results were analysed by developing metaphors from the data. These metaphors reflect women’s well-being as they present three unique career needs, namely challenge, balance, and authenticity, during their midlife career stage. Findings show how women’s projective identification with outdated gender role norms may perpetuate a gendered notion of work-life balance, which consistently challenges their well-being. Projective identifications are evident in introjected feelings of self-doubt, self-stereotyping, and in the tension between female employees’ personal and social identities. The study ultimately points to well-being as a dynamic phenomenon, which women sustain by engaging both positive and negative experiences and through identity tasks such as self-awareness, self-authorisation, self-regard, and authentic self-expression. These findings highlight the importance of creating self-reflective space in organisations to facilitate women’s psychological well-being.